Studying Abnormal Chromosomal Diseases Using Patient-Derived Induced Pluripotent Stem Cells - Hayashi, Yohei; Takami, Miho; Matsuo-Takasaki, Mami (Frontiers in Cellular Neuroscience, 2020)
Chromosomal abnormality causes congenital and acquired intractable diseases. In general, there are no fundamental treatments for these diseases. To establish platforms to develop therapeutics for these diseases, patient-derived induced pluripotent stem cells (iPSCs) are highly beneficial. To study abnormal chromosomal diseases, it is often hard to apply animal disease models because the chromosomal structures are variable among species. It is also difficult to apply simple genome editing technology in cells or individuals for abnormal chromosomes. Thus, these patient-derived iPSCs have advantages for developing disease models with multiple cell and tissue types, which are typically seen in the symptoms of abnormal chromosomal diseases. Here we review the studies of patient-derived iPSCs carrying abnormal chromosomes, focusing on pluripotent state and neural lineages. We also discuss the technological advances in chromosomal manipulations toward establishing experimental models and future therapeutics. Patient-derived iPSCs carrying chromosomal abnormality are valuable as cellular bioresources since they can indefinitely proliferate and provide various cell types. Also, these findings and technologies are important for future studies on elucidating pathogenesis, drug development, regenerative medicine, and gene therapy for abnormal chromosomal diseases.